Capitalization and the Theory of Local Public Finance - Yinger, John (Journal of Political Economy, 1982)
The Tiebout literature is incomplete, this paper argues, because it has not fully accounted for the capitalization of local fiscal variables into house values. The paper explains why capitalization arises, why it persists in long-run equilibrium, how it affects both residential location and the outcome of local voting, and why it interferes with the efficiency of a system of local governments. The analysis, which is based on the main Tiebout assumptions plus a property tax, combines a model of household bids in a housing market with a median-voter model of local public service determination.